Impact of IVLP on Mulberry Leaf and Cocoon Yield at Farmers’ Level - B.T. Sreenivas; A. Umesha; M. T. Himantharaj; Jaishankar; S.M.H. Qadri; C.K. Kamble (Journal of Agricultural Extension Management, 2025)
Dissemination of technology is considered more vital than the development of technology itself. Non availability of cutting edge and cost effective technologies to the primary stakeholders has been one of the major bottleneck affecting production and productivity. Though research organizations are acclaiming the development of a large number of technologies, the field acceptance or awareness of these technologies is rather poor resulting in a wide gap between potential or lab findings and field realization. The reasons attributed for non - availability/poor adoption of new technologies are many. Among them, defective approaches/one sided transfer of technology aspect appears to be a serious issue. As a result, the available technical know - how is reaching farmers in a diluted way leading to incomplete information. This results in partial adoption of new technologies leading to loss of interest and confidence of the farmers towards new developments. Based on the lessons learnt from the mistakes in the past, re-examining the existing technology transfer system appears to be imperative to bring in required reforms (Dandin et al., 2005)